The Efficacy of Mobile-Assisted Language Learning in Improving Learners’ Reading Skills in Relation to Metacognitive Strategy - Sudiatama; Sadaf Dehghani; Alex Zamorano (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Mobile-assisted language learning (MALL) is a mobile device-based approach that is utilized in language learning to enhance students' reading proficiency. As mobile devices have become the dominant mode of learning due to prevailing conditions, it has become increasingly necessary to employ adaptable learning processes that aim to improve students' reading skills through the use of metacognitive strategies. Although reading is one of several skills essential to learning English, in the current pandemic situation, it is impractical to teach it directly. Therefore, the MALL approach is imperative to adapt to the new teaching-learning process, particularly in the current pandemic scenario. This study endeavors to assess the application of MALL and its impact on students' reading skills by conducting both qualitative and quantitative research. Data collection methods in this study include observation, documentation, and field notes. The study involved one problematic class, to which researchers implemented the MALL application, followed by tests and interviews at the end of the study. The results indicate a significant increase in students' reading skills, along with ease of learning during the pandemic. Thus, this study highlights the efficacy of the MALL approach in improving students' reading skills and adapting to the pandemic-induced new teaching-learning process.